PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI MAHASISWA BERPRESTASI PROGRAM STUDI SISTEM DAN TEKNOLOGI INFORMASI DI UNIVERSITAS MUHAMMADIYAH KOTABUMI - Herlina, Oktari; Yulina, Yulina (LPPM Universitas Putera Batam, 2025)
Information systems play a crucial role in data management and providing useful information, including in the context of higher education. Student achievement, as an indicator of study success, needs to be managed effectively and efficiently. This study aims to develop a website-based student achievement data collection information system in the Information Systems and Technology Study Program, Muhammadiyah University of Kotabumi. Data collection methods used include literature studies to understand the concept of student achievement and information systems, as well as direct observation to analyze the current data collection process. The system development uses a waterfall model with stages of system analysis, design, implementation and system testing. The results of this website-based information system research are expected to be able to improve the efficiency and accuracy of student achievement data collection, as well as provide more complete and easily accessible information. This system is expected to support the improvement of the quality of student services in the Information Systems and Technology Study Program, Muhammadiyah University of Kotabumi